LINGUISTIC REVITALISATION AND THE DRAMA IN AFRICAN INDIGENOUS LANGUAGES - Alex, Patrick Charles (Sanata Dharma University, Yogyakarta, 2022)
This paper explores the drama written in indigenous African languages across many countries in Africa. It highlights the intellectual snobbery suffered by drama written in indigenous languages, probing the reasons behind the critical marginalization. It equally probes the elemental compositions of drama written in indigenous languages, investigating how oral elements revitalize and fertilize the dramatic works. The theoretical framework for this study was anchored on Ethnodramatics, a theory of indigenous drama projected by Affiah and Osuagwu while the inspirations which substantiate indigenous African languages as viable and effective linguistic mediums for dramatic creativity are derived from Ngugi wa Thiongo’s theoretical postulation on the language of African theatre in Decolonising the Mind: The Politics of Language in African Literature (1986). The paper reveals that traditional African drama in indigenous languages creatively utilizes oral resources and elements such as proverbs, riddles, mime, music, songs, dance, and other folk arts in ways that embellish and relive their drama. The paper concludes that by writing in indigenous languages, playwrights expand the resources and frontiers of African indigenous languages, a situation that nurtures and preserves them.